Pengaruh Pemasaran Media Sosial terhadap Keputusan Pembelian Somethinc di Kota Tangerang Selatan - Sabathini, Graciella; Nofiawaty, Nofiawaty; Putri, Yulia Hamdaini (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aims to determine the effect of social media marketing on purchasing decisions at Somethinc in South Tangerang City. This study is quantitative research with a survey method. The sampling technique used is non-probability sampling towards society in South Tangerang City. Data was collected through a questionnaire via google form for 100 respondents. This research used simultaneous tests (F-test), partial tests (T-test), and multiple linear regression analysis. The results showed social media marketing has a significant effect on purchasing decisions. Content creation, connecting, and community building partially effect purchasing decisions. Content sharing partially has no effect on purchasing decisions. Connecting has a dominant influence on the purchasing decision of Something in South Tangerang City. Keywords: social media marketing, purchase decisions